2017
DOI: 10.1039/c7ra02171b
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective fabrication of graphene-like nanosheets from natural microcrystalline graphite minerals by liquid oxidation–reduction method

Abstract: Graphene-like nanosheets were fabricated using natural microcrystalline graphite minerals (NMGM) instead of flake graphite (FG) using a liquid oxidation–reduction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In nature, there exist several magnetic ores consisting of naturally grown well‐oriented crystals. The exfoliation of these naturally occurring minerals has opened a new direction for the synthesis of 2D materials . Chromite is a representative of the naturally occurring oxide minerals on Earth belonging to the spinel group with general formula AB 2 O 4 (FeCr 2 O 4 ), where divalent A 2+ (Fe 2+ ) ions occupy tetrahedral sites and trivalent B 3+ (Cr 3+ ) ions occupy octahedral sites .…”
Section: The Structural Optimization Lattice Constant Of the Surface mentioning
confidence: 99%
“…In nature, there exist several magnetic ores consisting of naturally grown well‐oriented crystals. The exfoliation of these naturally occurring minerals has opened a new direction for the synthesis of 2D materials . Chromite is a representative of the naturally occurring oxide minerals on Earth belonging to the spinel group with general formula AB 2 O 4 (FeCr 2 O 4 ), where divalent A 2+ (Fe 2+ ) ions occupy tetrahedral sites and trivalent B 3+ (Cr 3+ ) ions occupy octahedral sites .…”
Section: The Structural Optimization Lattice Constant Of the Surface mentioning
confidence: 99%
“…The recent progress in synthetic strategies of 2D nanosheets were summarized by Yang et al, and approaches to the assembly of 2D nanosheets into 3D architectures were demonstrated by Shen et al [ 111 , 112 ]. Nowadays, graphene sheets are commercially available [ 113 ]. For example, GO can be bought from Aladdin ® (Shanghai, China) [ 85 ].…”
Section: Cost Fabrication and Limitationmentioning
confidence: 99%
“…At present, microcrystalline graphite is mainly used in low-end fields such as pencil lead and carburant for steelmaking. Recently, microcrystalline graphite is adopted to develop numerous products such as anode materials [19,20], electromagnetic absorbers [21], graphene nanosheets [22][23][24][25][26][27] and refractories [28,29]. However, it is difficult to achieve largescale application of microcrystalline graphite in the short term because of some technical barriers to break through.…”
Section: Introductionmentioning
confidence: 99%